PENDIDIKAN HUKUM KESEHATAN : HAK REMAJA ATAS KESEHATAN REPRODUKSINYA - Filu Marwati Santoso Putri; Bingar Hernowo (LPPM STIKES Madani Yogyakarta, 2019)
Women are required to be able to resist their vulnerability in an effort to voice the rights to reproductive protection that are protected by law. Basically, women's vulnerability is not only due to their biological factors, but also socially and culturally powerless to voice their sexual interests / rights for their safety, comfort and health. Economic, parenting and the environment factors can influence condition women's vulnerability. The phenomena that is often seen in PP Jamilurrohman is that many young women are very intense with their female friends. At first glance this is natural, but what needs to be worried is that unhealthy intimacy of same-sex adolescents will lead to intercourse/same-sex sex. Prevention of the incidence of same-sex sex in Islamic boarding schools needs to be sought by providing healthy life skills, especially about reproduction, which is done early so that adolescents are not carried away by the current deviated development. Providing health education about the rights of adolescents to reproduction will bring up the feminine side of a woman so that she will establish herself as a woman whose reproductive organs are inherent as her nature. The community involved in the education was all teenagers in the Jamilurrohman Putri Islamic Boarding School. Lecture followed by a focus group discussion was used as the methods. The results of community service activities show that young people were very enthusiastic in participating in activities and begin to understand women's reproductive health rights.